2012
DOI: 10.1097/der.0b013e318277ca3d
|View full text |Cite
|
Sign up to set email alerts
|

Patch Testing With Textile Allergens

Abstract: Supplementing the standard series with the textile series increased detection of textile allergies. In patients suspected of textile allergy, addition of the textile series is necessary for appropriate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 10 publications
2
28
1
Order By: Relevance
“…each, in their studies. 4,8,25 Thus, about 70% of the patients were allergic to at least 1 ingredient when tested to the same concentrations as used in the mix. These results also raise the question which is the optimal patch test concentration for the ingredients in the mix.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…each, in their studies. 4,8,25 Thus, about 70% of the patients were allergic to at least 1 ingredient when tested to the same concentrations as used in the mix. These results also raise the question which is the optimal patch test concentration for the ingredients in the mix.…”
Section: Discussionmentioning
confidence: 98%
“…14,15 However, in several previous studies, D Orange 1 was the most common allergen in the patients allergic to the mix. 3,13,24 In several other studies, however, D Blue 106 and D Blue 124 have been described as common allergens, 4 and many authors of studies on contact allergy to DDs have recommended them as screening allergens for textile dye dermatitis. 8,25 One possible reason for the divergent results compared to the outcome of our studies may be that D Blue 106 and D Blue 124 were tested at 0.3% each in the TDM in our present study but with a higher concentration 1% (pet.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several DDs have been used for patch testing in various studies to detect patients with contact allergy to textile dyes (1)(2)(3). In a study from the United States published in 2012 the authors concluded that supplementing the baseline series with a textile series would increase the detection of patients with textile dye allergies (4). Mixes of DDs have also been used in several studies in order to identify patients with contact allergy (3,(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 98%
“…However, ACD is still commonly seen with highly finished garments such as uniforms including water-resistant laboratory coats, zip-up greens worn by machinists and military wool garments [35,21]. In addition, a retrospective study conducted in 2012 showed that 8 % of patients who underwent screening patch testing between January 2000 and September 2011 using a textile series had positive patch reactions to melamine FA [36]. Thus, if these group of people are exposed to items which were made when FA releasing resins that release large quantities of FA were still being incorporated in clothing (e.g., vintage clothing and furniture (cotton upholstery)), there exists the potential to elicit ACD.…”
Section: Allergic Contact Dermatitismentioning
confidence: 98%